Developing a typology for local cattle breed farmers in Europe - Soini, Katriina; Diaz, C.; Gandini, G.; de Haas, Y.; Lilja, Taina; Martin-Collado, D.; Pizzi, F.; Hiemstra, S.J. (Blackwell, 2012)
Recognizing cultural diversity among local breed farmers is crucial for the successful development and implementation of farm animal genetic resources FAnGr conservation policies and programmes. In this study based on survey data collected in the EUropean REgional CAttle breeds project from six European countries, a typology of local breed farmers was designed and profiles for each of the farmer types were developed to assist these policy needs. Three main farmer types were constructed: production-oriented, product and service-oriented and hobby-oriented farmers. In addition, seven subtypes were characterized under the main types: sustainable producers, opportunists, multi-users, brand makers, traditionalists, pragmatists and newcomers. These types have many similarities to the productivist , multifunctional and post-productivist farmer types. The typology not only reveals the high level of diversity among local cattle breed farmers in Europe, which presents an opportunity for the in situ conservation of animal genetic resources, but also a challenge for policy to meet the differing requirements of the farmer types.
Keywords: Ma; maatiaislajikkeet; kasvatus; luokittelu; maanviljelijät; typology; farmers; local breeds; animal genetic resources; cattle breeds; farmer typology; cultural diversity